Further Remarks1 On The Impact Of Forward Sales On The Price Of Gold - H. L. Monro (The Southern African Institute of Mining and Metallurgy, 1993)
Al forward sales are made on the spot market, and are counter productive because they can only lower the price of gold, as one would expect from any additional supply of gold. Hedging against any further fall in the price of gold can be carried out on one of the World's Futures Exchanges in the same way as other commodities.